Clinical and prognostic value of determining the level of neopterin in patients with chronic heart failure with preserved ejection fraction - O. S. Polunina; L. P. Voronina; I. V. Sevostyanova; E. A. Polunina (Медицинский вестник Юга России, 2018)
Objective: to analyze the level of neopterin in patients with chronic heart failure (CHF) with a preserved fraction ejection fraction depending on the stage of the disease. Materials and methods: were examined 148 patients with CHF with preserved ejection fraction (50% and >) and 30 as a control group. Patients with CHF were divided into groups depending on the stage of CHF (from I to III). The level of neopterine was determined by the method of enzyme immunoassay in blood plasma. Results: in patients with CHF with preserved ejection fraction there was a tendency to increase the level of neopterin from stage I to stage III compared to the control group. In the group of patients with CHF IIB+III the level of neoplasm was statistically slightly lower compared to patients of stage I and IIA, but statistically signifi cantly higher than in the control group. Conclusion: it was revealed the change in the level of neopterin in patients with CHS with retained ejection fraction depending on the stage of the disease.